P-155 Silent voices: barriers and solutions to men engaging in palliative care group support. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Jackson, Matt; Popplestone-Helm, Sarah
Abstract : The hospice supports patients and families through a variety of group work programmes. However, engaging men in groups has proved challenging. A common trend was that males were uncomfortable and unwilling to participate in support if they felt under pressure to talk about their thoughts and feelings. To increase male engagement, a gardening group was set up at the hospice in partnership with Prostate Cancer UK. Male patients met weekly in the hospice gardens, participating in light gardening whilst taking time out and sharing their experiences. The group has grown and evolved over two years to twenty- five men attending weekly. They have developed a close bond, an ethos of care and support and a sense of fun, humour and enjoyment. One member described the group as 'my opportunity to be with my friends, I can share anything, laugh, cry, be silent, be silly, we understand each other.' The group evolved to include trips out, guest speakers and recently members have visited other groups and organisations sharing their experience of their group. A day is planned for the summer for men with life-limiting illnesses, encouraging new members to engage in palliative care group support. The success of this men's group has lead the hospice to consider why it has succeeded where others have not. Interviews and questionnaires with the members of this group, has enabled a greater understanding of barriers and concerns preventing men from engaging in group support. The group is self-directed and passionate; these men are articulate and passionate, willing to speak at national level to encourage others to participate in group support. They are determined to ensure longevity for the men who come after them, to be a voice for and to encourage 'the silent men', offering opportunity and durability for male groups such as theirs.